MADRASAH HEAD'S STRATEGY IN IMPROVING THE DIGITAL COMPETENCE OF MADRASAH ALIYAH TEACHERS IN BONDOWOSO STATE - Mohammad Bilutfikal Khofi (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
The digital competency gap among senior teachers (over 41 years old) is a seriouschallenge in supporting the implementation of the Merdeka Curriculum, especiallyat the State Islamic Senior High School (MAN) Bondowoso. This study aims toidentify and analyze the strategies of madrasah principals in improving the digitalcompetency of senior teachers so that they are able to adapt to technology-basedlearning. This study uses a qualitative approach with data collection techniques inthe form of in-depth interviews, participatory observation, and document analysis.Data were analyzed using the Miles and Huberman interactive model, whichincludes three stages: (1) data condensation through the process of selecting,focusing, simplifying, abstracting, and transforming data; (2) presenting data in theform of narratives and thematic matrices; and (3) drawing conclusions and verifyingthem repeatedly. Data validity is strengthened through the use of sourcetriangulation and member checking techniques to ensure the reliability,consistency, and accuracy of the data obtained. The results of the study show threemain strategies: (1) mapping digital competency needs through collaborativeassessments with universities to develop context-appropriate training modules; (2)implementation of routine training (in-service training) and independent learningbased on the Pintar Kemenag platform; and (3) digital-based teacher performancemonitoring through the e-Jurnal application that allows real-time monitoring andfeedback. These findings indicate that responsive and data-based leadership canaccelerate the transformation of digital competence among senior teachers. Thisstudy recommends replication of similar strategies in other madrasas as part ofstrengthening the implementation of the Merdeka Curriculum.